The Carpathian lingonberry, raspberry and blackberry fruit extracts feature variable antimicrobial efficiency - Mihok, Emőke; György, Éva; Máthé, Endre (Acta Agraria Debreceniensis, 2019)
Wild berry is an excellent source of phytonutrients and/or bioactive compounds associated with significant therapeutic properties, so that they have been utilized in folk medicine and traditional nutrition throughout centuries. Multiple health-promoting effects, such as anti-inflammatory, anti-diabetic, anti-heart and coronary disease properties were attributed to such wild berries. It has also been proved that berries could feature antimicrobial effects that could be of a great importance for the prevention of food-feed poisoning and fighting back antibiotic resistance. In this study, we investigated the antimicrobial properties of lingonberry (Vaccinium vitis-idaea), raspberry (Rubus idaeus) and blackberry (Rubus fruticosus) crude and ethanolic extracts prepared from fruits obtained from the spontaneous flora of Eastern Carpathian Mountains situated in Transylvania. The antimicrobial effect of crude and alcoholic extracts were assessed on four Gram-negative, five Gram-positive bacteria and one yeast species using the agar diffusion method. The studied bacteria can cause food or feed spoilage and foodborne diseases. Our results indicate the significant inhibitory effect of lingonberry extracts in the case of Gram-negative bacteria like Proteus vulgaris and Salmonella Hartford, while among Gram-positive bacteria the strongest inhibitory effect was observed for Bacillus species like B. cereus, B. subtilis, B. mojavensis and Micrococcus luteus. The raspberry and blackberry extracts featured milder inhibitory effects in the case of the studied bacteria species. Furthermore, we have studied the crude or ethanolic extract combinations associated antimicrobial effects synergistic/additive or antagonistic properties. Interestingly, the triple and double ethanolic extract mixes had stronger antimicrobial properties, whereas the crude extract mixes showed relatively reduced effects, if any. Our results indicate that the antimicrobial activity of studied fruit extracts obtained from wild berries can vary upon the applied extraction method and their combination formulae, so that all these considerations must be taken into account when such fruit extracts are considered for foodstuff development.